Valoración de la efectividad de interceptación con éxito de la portera de balonmano ante el lanzamiento tras la aplicación de un programa perceptivo-motor - Antunez Medina, A.; Urena Villanueva, F.; Velandrino Nicolas, A. P.; Garcia Parra, M. M. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2004)
The importance of perception in the collective sport in general, and in this particular case in handball, shows in the concrete throwing action, where the goalkeeper mustn`t only check the information joined the ball trajectory, but realize the throwing indicators of the players who do the throwing. This information is got by special sensorial receivers, what pointed the sight out like main character in our environment information reclaim.